Architecture from the frontline. - le Roux, Hannah; Southwood, David; Duker, Rob (Domus, 2008)
The photographs of Noero Wolff’s Red Location Museum suggest a post-traumatic state: all debris, dust and raw material, roaming children, and a tight, almost tense order that holds it all together. The building has striking composure, but it is the gritty setting that locates it in a compelling narrative. Noero Wolff won the commission in an open competition in 1998. The brief envisaged a museum and craft centre to celebrate South Africa’s history of struggle at its heart, in Red Location, an old township that had shown strong resistance to apartheid. The post-apartheid government developed such sites as a policy of representation: unable to bring immediate wealth to their vast numbers of impoverished supporters, it invested in symbolic projects for museums and parks that could bring the subsequent benefits of tourism.
Holcim Awards. Text: Le Roux,Hannah Design: Noero Wolff Architects Photos: Southwood,David; Duker,Rob
Keywords: Art Spaces, Human Rights